Therapeutic Perspectives in Type-1 Diabetes - Singh, Prachi; Kokil, Ganesh R.; Tupally, Karnaker R,.; Poddar, Kingshuk; Tan, Aaron; Venkatesan, Venky; Parekh, Harendra S.; Pastorin, Giorgio; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book provides critical insights into and appraisals of recent breakthroughs in type 1 diabetes modulation, with a particular emphasis on the potential impact of current prevention and treatment strategies. It also discusses recent successes and failures in clinical trials. Presenting an comprehensive overview of the disease, it is especially useful for newcomers in the field. It also includes illustrations, which make it easy for the reader to grasp the basic concepts involved. Furthermore, the tables include concise and easy-to-understand information on current clinical trials.
Introduction to Diabetes and Type 1 Diabetes -- Triggers Causing Type 1 Diabetes -- Predictors and Pathogenesis of Type 1 Diabetes -- Type 1 Diabetes: Past Present and Future Therapies.
Keywords: Biomedical engineering; Medicinal chemistry; Diseases; Biomedical Engineering and Bioengineering; Medicinal Chemistry; Diseases